(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Atmospheric pollution is one of the most serious environmental problems of modern times. To prevent it, it is necessary to reduce industrial emissions, switch to environmentally friendly energy sources, and apply advanced air purification technologies. Environmental sustainability can be achieved only with the participation of every person: it is essential to plant trees, rationally use transport, reduce waste, and promote recycling. Maintaining clean air plays a vital role not only for human health but also for the well-being of future generations.